Effect of Propolis on the Isolated Bacterial Infection on Covid-19 patient in Erbil City-Iraq - HUSSIEN, SHLER QASIM (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Propolis, a resin-like substance collected by honeybees, has long been known for its antimicrobial capabilities. Aim: To explore the antibacterial potential of ethanolic propolis extracts (EEP) against bacterial isolates obtained from COVID-19-infected patients in Erbil, Iraq. Methods: Clinical samples were obtained from 50 confirmed COVID-19 patients admitted to the Emergency Management Center (EMC) in Erbil. Standard microbiological methods were used for bacterial isolation and identification. Propolis extracts at a concentration of 1500 µg/mL were applied in wells on culture plates, and antibacterial activity was assessed by measuring zones of inhibition. Results: Out of 50 samples, 39 yielded positive bacterial cultures while 11 showed no bacterial growth. Among the isolates, 7 were Gram-positive and 23 were Gram-negative. Klebsiella species were the most frequently isolated Gram-negative pathogens, followed by E. coli and Pseudomonas spp. Staphylococcus aureus was the dominant Gram-positive isolate. No methicillin-resistant S. aureus (MRSA) strains were detected. The study demonstrated variable inhibition zones in response to different EEP concentrations. Conclusion: The ethanolic extract of propolis exhibited significant antibacterial effects against both Gram-positive and Gram-negative bacteria isolated from COVID-19 patients. The inhibition varied depending on bacterial species and EEP concentration.